Pointed warts: current treatment modalities and treatment compliance - A.A. Khryanin; Knorring G.Yu (LCC «Medicine-Inform», 2019)
Pointed warts: current treatment modalities and treatment compliance А.А. Khryanin1, G.Yu. Knorring2 1Novosibirsk State Medical University, Novosibirsk, Russian Federation 2A.I. Evdokimov Moscow State Medical and Dental University, Moscow, Russian Federation The prevalence of papillomavirus infection in Russia ranges from 29.1% to 44.8%. Various studies demonstrate that infection with human papillomavirus (HPV) is the major risk factor for cervical cancer (CC). Some studies establish the association between cervical intraepithelial neoplasia (CIN) and CC and certain variants of HLA class I and II genes. Polymorphism of HLA class I and II genes determines genetic predisposition to papillomavirus infection and the development of CIN and CC. Various subtypes of HPV were identified in 99.7% of biopsy specimens in CC patients. Recent findings suggest that HPV accounts for CC in 100%, rectal cancer in 90%, vulvar and vaginal cancer in 40%, oropharyngeal cancer in 12%, and oral cancer in 3%. The paper discusses important issues of papillomavirus infection epidemiology, diagnostic and treatment approaches to anogenital warts. Clinical case is described. Immunomodulating agent inosine pranobex (Isoprinosine®) provides HPV eradication, minimizes recurrence rate of anogenital warts, and prevents virus persistence with further chances of epithelial transformations both in men and women. Clinical trials on this agent has finished in 20th century, therefore, bibliography includes old references. Keywords: human papillomavirus, epidemiology, routes of transmission, anogenital warts, inosine pranobex, Isoprinosine®. For citation: Khryanin А.А., Knorring G.Yu. Pointed warts: current treatment modalities and treatment compliance. Russian Journal of Woman and Child Health. 2019;2(2):-101.